Evaluasi Formula Krim Minyak Biji Delima (Punica granatum L.) dan Uji Aktivitas Antioksidan dengan Metode Î²-Carotene Bleaching (Journal of Tropical Pharmacy and Chemistry, 2015)
Pomegranate seed oil has a potent antioxidant activity that is potential to be formulate into topical antioxidant dosage form. The purpose of this study is to formulate cream of pomegranate seed oil that physically stable, however have antioxidant activity. Cream w/o was formulated using Tween 80 - Span 80 as emulsifier. Evaluation of cream products includes determining pH and viscosity of the preparations stored for 4 weeks at room temperature, physical stability test by Freeze Thaw method which was carried out for 4 cycles in where 1 cycle consists of 48 hours at 4Â°C and 48 hours at 40Â°C. Antioxidant activity was tested by Î²-carotene bleaching method. The results of the research showed that all cream formulas containing pomegranate seed oil 1% were physically stable and can increase the comfortness in use on the skin. The antioxidant test results showed antioxidant activity of pure pomegranate seed oil and pomegranate seed oil as formulated in creams have antioxidant capacity with inhibition percentage of 73.41% and 52.80%, respectively. Based on these results it can be concluded that the antioxidant activity of pomegranate seed oil in cream decreased 0,3 times.